2022
DOI: 10.1111/xen.12766
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of nursing and theology faculty students on Xenotransplantation

Abstract: Background It is mentioned that students' opinions about xenotransplantation (XTx) have been explored in a limited manner. In particular, there is no literature in Turkey on Nursing and Theology students' perspectives on XTx. This research aimed to find out what Nursing and Theology students thought about XTx. Methods This descriptive and cross‐sectional study was conducted on students studying at the Theology and Nursing faculties. The study population consisted of 2.581 students educated in these faculties. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 27 publications
(43 reference statements)
0
18
0
Order By: Relevance
“…Previous studies also indicate that Muslims and Jews have a more conservative view on transplantation from pigs. And it is emphasized that religious authorities should pay special attention to this issue 16–20,26–28 . In the present study, the participants also expect clarification from religious authorities on transplantation from non‐haram animals.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…Previous studies also indicate that Muslims and Jews have a more conservative view on transplantation from pigs. And it is emphasized that religious authorities should pay special attention to this issue 16–20,26–28 . In the present study, the participants also expect clarification from religious authorities on transplantation from non‐haram animals.…”
Section: Discussionmentioning
confidence: 68%
“…Muslims, on the other hand, religiously emphasize that no part of the pig should be used for medical purposes 16 . It has also been reported that the Turkish community, the majority of which is Muslim, has a positive attitude towards xenotransplantation, while religious barriers exist 17 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations